1978
DOI: 10.1210/jcem-47-4-807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopamine Agonist (Lergotrile Mesylate) Therapy on Twenty-Four Hour Secretion of Prolactin in Treated Parkinson's Disease*

Abstract: Plasma PRL was measured at 20-min intervals in six patients with Parkinson's disease under various treatment protocols. In addition, 24-h mean GH levels were measured. The results of these studies showed that two untreated patients with Parkinson's disease had normal 24-h mean PRL levels with the normal increase during sleep. During chronic treatment with L-dopa-carbidopa (Sinemet), the 24-h PRL level was 12.8 +/- 4.9 ng/ml (mean +/- SD) and there was persistence of augmented PRL secretion during sleep. The 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Turkington [11] reported a successful suppression of hPRL levels in hyperprolactinemic patients fol lowing 6 months treatment with L-dopa, whereas Malarkey et al [ 12] and Bell e\ al. [13] demonstrated an intact circadian rhythm of serum prolactin concentration in L-dopa treated parkinsonian patients.…”
Section: Introductionmentioning
confidence: 85%
“…Turkington [11] reported a successful suppression of hPRL levels in hyperprolactinemic patients fol lowing 6 months treatment with L-dopa, whereas Malarkey et al [ 12] and Bell e\ al. [13] demonstrated an intact circadian rhythm of serum prolactin concentration in L-dopa treated parkinsonian patients.…”
Section: Introductionmentioning
confidence: 85%
“…However, short-term dopaminergic therapy in normal humans1618,26 showed variable effects on anterior pituitary hormones but consistent PRL suppression. Similar PRL suppression has been demonstrated in subjects with IPD on chronic dopaminergic therapy 25,2729. A more recent study of chronic dopaminergic therapy in patients with IPD showed marked inhibition of PRL and peripheral growth hormone resistance 21…”
Section: Discussionmentioning
confidence: 54%
“…Similar PRL suppression has been demonstrated in subjects with IPD on chronic dopaminergic therapy. 25,[27][28][29] A more recent study of chronic dopaminergic therapy in patients with IPD showed marked inhibition of PRL and peripheral growth hormone resistance. 21 There were imitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also noticed that chronic administration of Madopar induced changes in Prl responses possibly related to defective TIDA function, whereas the function of hypothalamic DA tended to be preserved after Sinemet treatment [171]. In a study on the regulation of PRL secretion, Bell et al found that 2 nontreated PD patients had a normal 24-h mean PRL concentrations and exhibited normal increases during sleep, indicating dopamine deficiency in PD does not influence all dopaminergic neurons [172][173][174].…”
Section: Levodopa Benserazide and Carbidopamentioning
confidence: 99%